A Comparative Mechanistic and Kinetic Study of the Synthesis Reaction of 3, 4, 5‐Substituted Furan‐2(5H)‐ones: Solvent Effect. Issue 19 (17th November 2016) - Habibi‐Khorassani, Sayyed Mostafa; Shahraki, Mehdi; Dehdab, Maryam
Abstract: Solvent can influence kinetics and mechanism of a chemical reaction. Herein, the different behavior of solvent media on the competitive mechanism between benzaldehyde (1), 4‐ethylaniline (2) and diethyl acetylenedicarboxylate (3) has been described when solvent was changed from acidic pH range (formic acid in the previous work) to values near or above neutrality (ethanol in the recent work). Experimental documents was obtained using UV‐vis and stopped‐flow spectrophotometry techniques. The results showed that the reaction in the presence of ethanol followed second order kinetics with respect to benzaldehyde (1) and 4‐ethylaniline (2), while it was second order kinetics in previous work (formic acid) in relation to 4‐ethylaniline (2) and diethyl acetylenedicarboxylate (3) . A speculative mechanism involving five steps was proposed that the first step encountered the largest energy barrier as a rate‐determining step ( RDS ). Furthermore, the influences of temperature and concentration on the reaction rate were investigated. Activation parameters ( Δ H ≠, Δ S ≠ and Δ G ≠ ) along with kinetics values (kove and E a ) were determined. The reaction was entropy controlled in ethanol as a solvent. Abstract : Kinetic results together with the detailed mechanistic studies of the synthesis reaction of 3, 4, 5‐substituted furan‐2(5H)‐ones have been reported based on a global kinetic analysis methodology using the stopped‐flow and UV‐vis spectrophotometry techniques. A completely different behavior of a comparative mechanism affected by solvent was described and also a speculative mechanism involving five steps was confirmed based upon the steady‐state approximation and experimental data.